Career Guidance Services in an Effort to Improve Self Efficacy of Vocational High School Students - Assahrawiza, Assahrawiza; Afdal, Afdal; Hariko, Rezki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Career planning needs to be prepared before students jump directly into the world of careers. Career planning needs to be based on the potential that students have so that there is no conflict between the chosen career and the potential that exists in students. However, not all students can plan their careers well, so problems arise related to less than deal self-efficacy students in career choices. The purpose of this study was to determine the role of career guidance services in increasing the self-efficacy of class XII students in career selection. This research includes field research (Field Research) with the type of qualitative research and uses descriptive methods. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results showed that the condition of students' self-efficacy in choosing a career was marked by confusion in choosing a career, lack of self-confidence, and not knowing self-potential. Increasing students' self efficacy in choosing careers can be done with career guidance services carried out in groups, the stages include: 1) initial stage, 2) intermediate stage, 3) activity stage, and 4) final stage. The results of the career guidance service are that there is an increase resulting from the career guidance process, namely students can plan their careers well and can choose a career field that suits their potential. Keywords: Counseling Guidance; Self Efficacy; career selection.